Entropy-Based Analysis of the Impact of Environmentally Sensitive Elements on Groundwater Quality of the Ameka Region of Southeast Nigeria: Medical Geology Implications - Egbueri, Johnbosco C.; Ameh, Peter D.; Enyigwe, Monday T.; Unigwe, Chinanu O. (Analytical letters, 2021)
Understanding the impact of natural and modified environment on human health is a subject within the scope of medical geology. Ameka and its environs in southeastern Nigeria is known for intensive mining and agricultural activities that frequently predispose water resources to pollution by environmentally sensitive elements (ESEs). The present study analyzed the groundwater quality and associated probabilistic human health risks due to ESEs in Ameka area, using multiple indices and a novel health risk assessment framework, HHRISK. Entropy-weighted water quality index and other geochemical evaluation indices (including pollution index, enrichment factor, index of geoaccumulation, pollution index of groundwater, and quantification of contamination) revealed that all the groundwater samples from hand-dug wells and boreholes were extremely polluted and hence unsuitable for drinking. The HHRISK model was utilized for ingestion and dermal exposure routes assessments. Results showed that all the samples pose very high carcinogenic and non-carcinogenic health risks. With respect to aggregated non-carcinogenic HHRISK, the order of health threat impact of the ESEs for children and adult populations is predicted as Cd > As > Se > Co > Ni > Pb > Mn > Zn > Cu > Fe. However, aggregated cancer risk for both populations followed the trend Ni > Cd > As > Pb. Furthermore, cumulative non-carcinogenic risk (HRQ cum ) and carcinogenic risk (CR cum ) scores (for children and adults) exceeded standard limits in all the samples. However, the scores obtained for the adults were generally lower, implying that the children population is more vulnerable to both non-carcinogenic and carcinogenic health risks. Thus, there is urgent need to adopt environmentally-friendly pollution mitigation measures in the Ameka area.